Analisis Pengaruh Ekonomi Digital Terhadap Pertumbuhan Ekonomi di Indonesia: Model Data Panel - Ahmad Albar Tanjung; M Syafii; Sufhia Br Tarigan; Widya Gustriani Harahap (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of the digital economy has seen from the number of internet users (JPI), the value of e-commerce transactions (NT), and the total growth of e-commerce businesses (JU), both partially and simultaneously, on economic growth (PE) in Indonesia. Indonesia. The type of research used is quantitative. The data used in this study is panel data which is a combination of time series and cross section data where the annual time series data is 2018-2020 and the cross section consists of 34 provinces in Indonesia using the E-Views 10 tool. Data sources the data used are from the Central Statistics Agency (BPS) and the Association of Indonesian Internet Service Providers (APJII). The analysis method adopted is the fixed effect model of panel data regression method.The results showed that the independent variables Transaction Value and total Growth of e-commerce businesses had a positive and significant effect on the dependent variable of economic growth or PE, while the JPI variable had a negative and significant effect on economic growth.